Education, Media and Sexuality Health Services for Girls and Women - 20 Years Experience of China's Policy and Practice. - Bu, Wei (Education and development for rural women and girls in China series., 2014)
China's experience in the field of women and girls' education and development has not been adequately summarized and shared with the international community. To fill the gap and celebrate the 20th anniversary of the 4th World Conference on Women, this book systematically summarizes and disseminates the strategies and good practices regarding women's and girls' education and development in China, so as to present national experiences in the promotion of rural women's empowerment and gender equality. The book reviews the policies and actions taken by the Chinese government, international organiz.